Social networking - Espejo, Roman (Teen rights and freedoms, 2012)
"Social Networking: Understanding the Legal Issues of Social Networking Sites; Social Networks Should Be Banned at Libraries and Schools; Social Networks Should Not Be Banned at Libraries and Schools; Students' Rights on MySpace Should Be Protected; Banning Social Networks Would Be Counterproductive; Laws Against Cyberbullying Are Necessary to Protect Young People; Laws Against Cyberbullying May Infringe on Free Speech; A College Student Discusses How Cyberbullying Threatened Her Education; Social Networks May Erode Young People's Privacy; Young People Are More Protective of Their Privacy on Social Networks; The Federal Trade Commission Protects the Privacy of Teens on Social Networks; Young People and Free Speech Can Be Protected on Social Networks; Court Rulings on Social Networks, Teens, and Free Speech Rights Are Unclear; Teens With Web Sites May Not Be Liable for Content by Third Parties; Defamation and Fraudulent Profiles on Social Networks; Copyright Laws Must Be Changed for Youths and Students on the Internet"--